Mutations in MICAL‐1cause autosomal‐dominant lateral temporal epilepsy. Issue 3 (13th March 2018) - Dazzo, Emanuela; Rehberg, Kati; Michelucci, Roberto; Passarelli, Daniela; Boniver, Clementina; Vianello Dri, Valeria; Striano, Pasquale; Striano, Salvatore; Pasterkamp, R. Jeroen; Nobile, Carlo
Abstract : Objective: Autosomal‐dominant lateral temporal epilepsy (ADLTE) is a genetic focal epilepsy characterized by auditory symptoms. Two genes, LGI1 and RELN, encoding secreted proteins, are implicated in the etiology of ADLTE, but half of the affected families remain genetically unsolved, and the underlying molecular mechanisms are yet to be clarified. We aimed to identify additional genes causing ADLTE to better understand the genetic basis and molecular pathway underlying this epileptic disorder. Methods: A cohort of Italian ADLTE families was examined by whole exome sequencing combined with genome‐wide single‐nucleotide polymorphism‐array linkage analysis. Results: We identified two ADLTE‐causing variants in the MICAL‐1 gene: a p.Gly150Ser substitution occurring in the enzymatically active monooxygenase (MO) domain and a p.Ala1065fs frameshift indel in the C‐terminal domain, which inhibits the oxidoreductase activity of the MO domain. Each variant segregated with ADLTE in a single family. Examination of candidate variants in additional genes excluded their implication in ADLTE. In cell‐based assays, both variants significantly increased MICAL‐1 oxidoreductase activity and induced cell contraction in COS7 cells, which likely resulted from deregulation of F‐actin dynamics. Interpretation: MICAL‐1 oxidoreductase activity induces disassembly of actin filaments, thereby regulating the organization of the actin cytoskeleton in developing and adult neurons and in other cell types. This suggests that dysregulation of the actin cytoskeleton dynamics is a likely mechanism by which MICAL‐1 pathogenic variants lead to ADLTE. Ann Neurol 2018;83:483–493